Incidence of Medically Compromised Patient’s attending Oral Surgery Department for Extraction and Minor Surgery - Bokhari, Syed Kamran (International Journal of Psychosocial Rehabilitation, 2014)
Objectives:Minor Oral Surgery and Teeth Extraction in medically compromised patients need special care and care. Aim of this study was to analyse the incidence of medically compromised patients attending oral surgery department for teeth extraction and minor oral surgery. Materials and Methods:Patients with medically compromised conditions were sub-divided into. This study was conducted with the following aim & objectives: 1.To assess the incidence of medical conditions in patients 2. To assess the type of medical condition and age group 3. To estimate the statistical significance and compare with similar studies. Results: Diabetes mellitus was the most common Co morbidity Affecting the people which was found to be statistically significant (p=<0.05). The second frequent medical condition in our population was hypertension and the third prevalent medical condition was anemia which was more commonly observed in females (31.42%) which were found to be statistically significant (p=<0.05). Conclusion:The management of medically compromised patients in dental care is a specialty in itself. A dentist must master it in order to provide proper and comprehensive care through referral, treatment modification, and appropriate drug modifications. At the same time, the dentist must be well prepared to tackle any undue consequences or complications. Gathering complete medical history and careful clinical examinations are imperative to avoid complications and render effective dental care.